Promoting Interculture in Participation in German Urban Planning: Fields of Action for Institutional Change - Huning, Sandra (2021)
Germany has been a host country for immigrants for a long time, but an institutional transformation to promote interculture in urban public administration in general, and participation in urban planning in particular, has only just begun. This article addresses institutional frameworks and proposes strategic elements for interculture in participation, based on transdisciplinary, participatory, and transformative research in two German cities. Interculture means overcoming access barriers, based on cultural norms and stereotypes, to open up participation for groups who have been underrepresented so far. The article presents four types of barriers to interculture: a selective implementation of interculture guidelines, an institutional culture that leaves room for ‘othering’ of immigrant groups, top-down definitions of participation procedures, and an inter-departmental division of labour. In response to these barriers, we elaborate two fields of action: the establishment of spaces for reflexivity and of a ‘phase zero’ that helps to build trust and long-term relationships with immigrant communities. These fields of action do not offer any concrete road map. Instead, they focus on the institutional context for action, its structures, self-understandings, and the scope for individual action, and are thus much harder to address. The transformative, participatory, and transdisciplinary research setting bears both challenges and potential, but the article argues that it is beneficial for urban studies in light of the challenges that cities are facing.